Redemption in Kind and Mutual Fund Liquidity Management - Agarwal, Vikas; Ren, Honglin; Shen, Ke; Zhao, Haibei (Review of Financial Studies, 2023)
Abstract Open-end mutual funds can use redemption in kind to satisfy investor redemptions by delivering securities instead of cash. We find that funds that reserve their rights to redeem in kind experience less redemption after poor performance. Evidence from actual in-kind transactions reveals several unique mechanisms for redemption in kind to mitigate fund runs, including the delivery of more illiquid stocks and stocks with greater tax overhang. Funds suffer less from the adverse impact of outflows on their performance. However, redeeming investors bear significant liquidation costs when they sell securities, costs associated with destabilization in the prices of these securities. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.